Dampak Tata Kelola Perusahaan Terhadap Kebijakan Pembayaran Dividen Pada Perusahaan Manufaktur - Henny S. Lestari, Veren V. Natalie, Yunita Kusumaningrum, (Jurnal Ekonomi, 2021)
This research paper scrutinizes the influence of corporate governance which was one of the determinants of dividend payments policy. A total of 195 manufaturing companies listed on Indonesia Stock Exchange used for sampel on this research and using 5 years period start from 2016-2020. The data used in this paper is secondary data and the sampling method is using purposive sampling method. The panel data regression methode is used for this research to test the influence of independent variable toward dependent variable. The outcame of this study reveal that board gender diversity and return on asset ratio (ROA) have negative effect on dividend payout ratio (DPR). However, board size and leverage have no effect on dividend payout ratio (DPR). This research expected to provide an information and overview to investor in making investment decision to pay attention to coporate governance because it's has an impact on the firm's dividend payout policy.